2020
DOI: 10.1021/acsbiomaterials.9b01806
|View full text |Cite
|
Sign up to set email alerts
|

Decoration of Material Surfaces with Complex Physicochemical Signals for Biointerface Applications

Abstract: The surface properties of biomaterials are crucial at controlling biological interactions. Cells or tissues sense different stimuli from surfaces and respond accordingly. A number of studies have reported that fabricating complex stimuli-presenting surfaces is beneficial for mimicking and understanding the in vivo scenario where multi-physicochemical cues are present. Biological responses toward these surfaces could be either negative, such as immune responses, or positive, such as tissue regeneration. An idea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 143 publications
0
26
0
Order By: Relevance
“…Traditional 2D cell cultures, utilizing homogeneous inert substrates such as glass or tissue culture plastics, are often used to rapidly screen novel treatments but fail to recreate the complex multi-cellular environments seen within the body ( Mirbagheri et al, 2019 ). One strategy to overcome this limitation is the selective deposition of microscale topographical and chemical cues on homogeneous 2D cell culturing platforms ( Bettinger et al, 2009 ; Mirbagheri et al, 2019 ; Zhang K. et al, 2019 ; Shi et al, 2020 ). These highly structured surfaces composed of various patterns, also known as 2.5 dimensional objects, have been recognized as a promising tool for controlling cells behavior and function, including attachment, migration, proliferation, and differentiation, with cell morphological and functional responses greatly depending on the cell type as well as the pattern type and dimensions ( Mirbagheri et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditional 2D cell cultures, utilizing homogeneous inert substrates such as glass or tissue culture plastics, are often used to rapidly screen novel treatments but fail to recreate the complex multi-cellular environments seen within the body ( Mirbagheri et al, 2019 ). One strategy to overcome this limitation is the selective deposition of microscale topographical and chemical cues on homogeneous 2D cell culturing platforms ( Bettinger et al, 2009 ; Mirbagheri et al, 2019 ; Zhang K. et al, 2019 ; Shi et al, 2020 ). These highly structured surfaces composed of various patterns, also known as 2.5 dimensional objects, have been recognized as a promising tool for controlling cells behavior and function, including attachment, migration, proliferation, and differentiation, with cell morphological and functional responses greatly depending on the cell type as well as the pattern type and dimensions ( Mirbagheri et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…These highly structured surfaces composed of various patterns, also known as 2.5 dimensional objects, have been recognized as a promising tool for controlling cells behavior and function, including attachment, migration, proliferation, and differentiation, with cell morphological and functional responses greatly depending on the cell type as well as the pattern type and dimensions ( Mirbagheri et al, 2019 ). As such, these topographical substrates are capable of better mimicking the natural extracellular matrix and have shown great promise as in vitro experimental test platforms for applications within both drug discovery and disease modeling in which tissue models should adequately recapitulate the complexity of natural cell organizations ( Bettinger et al, 2009 ; Mirbagheri et al, 2019 ; Zhang K. et al, 2019 ; Shi et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Presence of intrinsic functional group in a compound allows easy functionalization which serve as a linker for further reaction, chain transfer agent, initiator and monomers used for particular use 2 . Advancement of nanotechnology found utility for development of functional material for photodynamic therapy, diagnosis, 3 therapeutic delivery, biological application, anticancer drug delivery, bioelectronics and biointerface applications 4 . The most commonly used functionalization strategies used in chemical methods are esterification, amidation, azide‐alkyne click reaction, atom transfer radical polymerization, reversible addition‐fragmentation chain‐transfer polymerization, ring opening polymerization (ROP) and other modern polymerization method used for synthesis of multifunctional material 5 .…”
Section: Introductionmentioning
confidence: 99%
“…We therefore introduced a vapor-based synthesis of a porous material that comprised poly- p -xylylene as the backbone matrix and was equipped with methyl propiolate functionality to perform a metal-free 1,3-dipolar cycloaddition click reaction from the interface. The construction of the porous material is based on our previous discovery that the deposition of poly- p -xylylene on sublimated ice templates (instead of non-sublimated substrates) can result in the production of a three-dimensional and porous poly- p -xylylene material [ 18 ], and the shape, size, and inner porous structure of the porous polymer products are also customizable [ 19 , 20 ]. It has also been reported that the deposition of poly- p -xylylenes can be functionalized by using substituted [2,2]-paracyclophanes as the precursors during the chemical vapor deposition (CVD) polymerization process [ 21 ], and a variety of functional groups, such as amine, hydroxyl, vinyl, alkyne, maleimide, aldehyde, and disulfide groups, which were successfully produced to form functionalized poly- p -xylylene coatings and performed tasks for biointerface engineering [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%